Human adipose-derived mesenchymal stem cell-derived exosomes induce epithelial remodeling and anti-scar healing revealed by single-cell RNA sequencing - Yu Fu; Jun-ling Xie; Xing-liao Zhang; Guang-ming Xie; Xin-Min Zhang; Yao-ting Han; Meng-meng Xu; Jing Zhang; Jun Zhang (Journal of Nanobiotechnology)
Abstract The scar-free healing remains a clinical challenge, and requires the concerted efforts of multiple cell types, such as keratinocytes and fibroblasts. Exosomes derived from human adipose-derived mesenchymal stem cells (hADSC-Exos) have emerged as a promising therapeutic option. Nonetheless, a thorough understanding of the mechanisms underlying regenerative healing in response to hADSC-Exos treatment is still lacking. Here, we performed high-resolution single-cell RNA sequencing analysis of adult wild-type and hADSC-Exos-treated mice at postoperative day (POD) 14. hADSC-Exos influenced epithelial cells and fibroblasts, leading to scar-free wound healing. Among the epithelial cell subtypes, Lymphoid enhancer binding factor 1 high proliferating keratinocytes (prolif KC) are particularly remodeled by hADSC-Exos. Prolif KC exhibit epithelial-mesenchymal plasticity (EMP). Cell-cell communication between keratinocytes and fibroblasts during anti-scar healing is modulated by tumor growth factor-β1, which promotes the EMP transition cascade. hADSC-Exos may inhibit wound fibrosis through the 14-3-3 zeta-YES-associated protein-Hippo signaling pathway. This study enhances our understanding of epithelial cell diversity and interactions in wound healing, highlighting hADSC-Exo-induced prolif KC as a potential reprogramming target. These epithelial cells are promising therapeutic targets for improving wound-healing strategies.